Pursuing A Circular Economy: Examining the Solid Waste Separation Practices of Restaurants in Madina of The La Nkwantanang-Madina Municipality (LANMMA) - Obeng-Odei, I. (University of Ghana, 2022)
Sustainable waste management has been particularly challenging for Ghana. There have been studies aimed at understanding and improving waste management systems however, most are focused on households; neglecting other sectors and their contributions to the waste situation in Ghana. This study pinpoints sustainable waste management practices in the restaurant industry of Madina – La Nkwantanang Municipality and how they can leverage the attainment of a circular economy paradigm of development. The study assessed restaurant personnel’s knowledge on the benefits of solid waste separation and examined the enabling and constraining factors of the adoption of waste separation and eco-friendly alternatives in the industry. One hundred and fifty-six (156) restaurant managers participated in the survey, which employed the use of semi-structured questionnaires. In addition, key resource persons from the municipal assembly and waste collectors were purposively sampled and interviewed. The results of the study revealed that there is an absence of waste separation agenda specific to the restaurant sector in Madina. Also, there is limited knowledge and practice of waste separation in restaurants in the study area; although, a significant number of restaurants are willing to incorporate environmentally sustainable practices in their business strategies. As per the findings, the study recommends educational and awareness campaigns for personnel of restaurants in Madina, the formulation and implementation of waste management policies for the sector, the provision of incentives like machinery and tax subsidies and the involvement of the private sector through partnerships.
MA. Development Studies
Keywords: Sustainable waste managemen; Ghana; restaurant industry; Madina